The efficacy of a stabilized chlorine dioxide mouthwash among selected group of patients - Gervasio NC (The Journal of the Philippine Dental Association)
This clinical trial aimed to test the efficacy of DurafreshSUPTM; _SUP mouthrinse and gel on periodontal pockets, halitosis and oral sores among elderly Filipinos and Filipino adults. Thirty two subjects (age ranging from 31 to 81) from two sample populations were able to complete the study. Pocket Probing Depth (PPD) using the Ramjford`s Index Teeth oral sore healing and halitosis scores were recorded . The clinical trial was run for four weeks and 5 measurements of each evaluation parameter were taken: baseline, and every week after the start of the rinsing regiment thereafter up to 4 weeks. Means for each clinical parameter were computed and analyzed using Student`s t-test to determine whether there is significant change in the evaluation parameters over time. Results showed that 1) pocket probing depth seemed to improve with the use of DurafreshTM mouthrinse 2) DurafreshTM oral gel hastened the healing of oral sores and provided some of palliative effect 3) halitosis was significantly decreased with the use of DurafreshTM mouthrinse.